Characterization of a Mouse Recombination Hot Spot Locus Encoding a Novel Non-Protein-Coding RNA - Nishant, K. T. (American Society for Microbiology, 2004)
Our current knowledge of recombination hot spot activity in mammalian systems implicates a role for both the primary DNA sequence and the nature of the chromatin domain around it. In mice, the only recombination hot spots mapped to date have been confined to a cluster within the major histocompatibility complex (MHC) region. We present a high resolution analysis of a new recombination hot spot in the mouse genome which maps to mouse chromosome 8 C-D. Haplotype diversity analysis across 40 different strains of mice has enabled us to map recombination breakpoints to a 1-kb interval. This hot spot has a recombination intensity that is 10- to 100-fold above the genome average and has a mean gene conversion tract length of 371 bp. This meiotically active locus happens to be flanked by a transcribed region encoding a non-protein-coding RNA polymerase II transcript and the previously characterized repair site. Many of the primary DNA sequence features that have been reported for the mouse MHC hot spots are also shared by this hot spot locus and in addition, along with three other MHC hot spot loci, we show a new parallel feature of association of the crossover sites with the nuclear matrix.